Familial risk of prostate cancer in Iceland - Eldon, B J; Jonsson, E; Tomasson, J; Tryggvadottir, L; Tulinius, H (BJU International, 2003)
OBJECTIVE: To estimate the risk of prostate and other types of cancer among relatives of Icelandic men diagnosed with prostate cancer over a 5-year period. PATIENTS AND METHODS: The risk ratio (RR) was used to estimate the risk among relatives of 371 patients with prostate cancer, all of whom lived in Iceland and were diagnosed when alive over a 5-year interval (1983-7). Information on cancer incidence was obtained from the population-based Icelandic Cancer Registry, and information on families from a comprehensive genealogical database covering the population of Iceland. RESULTS: First-degree male relatives were at a 1.7-fold greater age-adjusted risk of prostate cancer (1832 men; 95% confidence interval, CI, 1.28-2.34). The risk was independent of proband's age at diagnosis. First-degree male relatives of patients who died from prostate cancer were at a statistically significantly greater risk of the disease (784 men; RR 2.17; 95% CI 1.34-3.53) and relatives of patients with incidental disease (T1a) were at a greater risk but not statistically significant so (261; RR 1.86; 95% CI 0.75-4.58). Female first-degree relatives were not at greater risk of breast cancer. The risk of kidney cancer was higher in first- and second-degree female relatives, with an RR (n, CI) of 2.50 (1780, 1.10-5.66) and 2.67 (5534, 1.04-6.81), respectively. The risk of kidney cancer was not statistically significantly greater in male relatives. CONCLUSION: Family history is a risk factor for prostate cancer in Icelandic men. The risk is potentially higher for relatives of patients who die from the disease. Female relatives are not at greater risk of breast cancer but they may be at greater risk of kidney cancer.